Bioaccumulation of long-term atmospheric heavy metal pollution within the Carpathian arch: monumental trees and their leaves memoir - Vasile D; Enescu R; Apafaian A; Coman S; Scarlatescu V; Crisan V (iForest - Biogeosciences and Forestry)
Atmospheric pollution is a major problem in urban environments. Pollutants with various sizes of particulate matter result from long-term anthropogenic sources, including industrial emissions and the combustion of fossil fuels by vehicles and commercial and residential buildings. Pollutants affect both humans and green areas. Trees are good indicators of pollution due to their longevity, easy identification, and geographical distribution in urban areas. Recently, due to climate change, all EU member states have agreed to measure heavy metal pollution in urban areas using plants as bioindicators. This study aimed to analyze heavy metal concentrations (Pb, Cd, Mn, Fe, Cu, Zn) in the leaves of monumental trees (both evergreen coniferous and deciduous) in the Carpathian Arch. Leaf samples were collected in the summer of 2022 from 37 specimens across 12 sites in nine counties - Alba, Brasov, Harghita, Mures, Sibiu, Satu Mare, Bistrita Nasaud, Maramures, and Cluj. The leaf heavy metal contents correlated with a low level of atmospheric pollution. Of the six heavy metals analyzed, only four were highly accumulated in the leaf samples and exceeded the toxicity threshold. Of the nine counties sampled, heavy metal pollution above the toxicity threshold was detected only in two sites - the city of Baia Mare, Maramures county (Zn and Cd), and the city of Cluj-Napoca, Cluj county (Fe, Zn, Cd, and Cu). The response of the tree species to changes in atmospheric heavy-metal concentrations confirmed that trees are suitable bioindicators of air pollution in urban areas. Monumental trees can also be used for environmental restoration and to promote sustainable urban development, decrease pollution, and increase urban environmental health.